2019
DOI: 10.1126/sciadv.aav9492
|View full text |Cite
|
Sign up to set email alerts
|

Fully soluble self-doped poly(3,4-ethylenedioxythiophene) with an electrical conductivity greater than 1000 S cm −1

Abstract: Wet-processable and highly conductive polymers are promising candidates for key materials in organic electronics. Poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) is commercially available as a water dispersion of colloidal particles but has some technical issues with PSS. Here, we developed a novel fully soluble self-doped PEDOT (S-PEDOT) with an electrical conductivity as high as 1089 S cm−1without additives (solvent effect). Our results indicate that the molecular weight of S-PEDOT is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 49 publications
3
115
0
Order By: Relevance
“…The synthesis of PEDOT:PolyDADMA FSI and PEDOT:PolyDADMA TFSI were carried out following a previously reported procedure [ 29 ], by oxidative polymerization in an acidic medium. It was previously reported that using an acidic medium can enhance the doping of PEDOT chains [ 30 ]. EDOT (0.3 mL, 2.81 mmol) and 20 wt% PolyDADMAC (1.92 mL, 2.48 mmol) were dispersed in 50 mL of 0.1 M HCl aqueous solution.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of PEDOT:PolyDADMA FSI and PEDOT:PolyDADMA TFSI were carried out following a previously reported procedure [ 29 ], by oxidative polymerization in an acidic medium. It was previously reported that using an acidic medium can enhance the doping of PEDOT chains [ 30 ]. EDOT (0.3 mL, 2.81 mmol) and 20 wt% PolyDADMAC (1.92 mL, 2.48 mmol) were dispersed in 50 mL of 0.1 M HCl aqueous solution.…”
Section: Methodsmentioning
confidence: 99%
“…The dispersion of colloidal PEDOT particles surrounded by PSS can limit the formation of intimate stacking and connections between adjacent PEDOT chains, influencing charge transport and necessitating the introduction of additives to improve conductivity. [ 201–203 ] The fixed nature of the PSS counterion means the PEDOT polymer cannot achieve a fully neutral state, impacting the on–off ratio of devices. [ 180 ] The complexity of the material makes it a challenging model system to probe charge transport behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…reported a self‐doped PEDOT variant they call S‐PEDOT, with an electrical conductivity of over 1000 S cm −1 . [ 201 ] They found the conductivity is highly dependent on the concentration of the S‐EDOT monomer during polymerization, which in turn impacts crystallite formation in thin films ( Figure ). In general, the conjugated polyelectrolyte approach is not limited to PEDOT and has also been demonstrated in OECTs fabricated from a polyelectrolyte derivative of polythiophene.…”
Section: Methodsmentioning
confidence: 99%
“…[54] The use of reported water soluble EDOT derivatives, bearing carboxyl or sulfonate group is particularly attractive. [63][64][65] It is therefore likely that optimization of this process will allow the future synthesis of tetra-and penta-oligomers with sufficient solubility for gelation.…”
Section: Oligoedot Crosslinked Hydrogelsmentioning
confidence: 99%